2017
DOI: 10.1016/j.jenvman.2017.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of an entire ceramic kiln under actual operating conditions for the energy efficiency improvement

Abstract: The paper focuses on the analysis of an industrial ceramic kiln in order to improve the energy efficiency and thus the fuel consumption and the corresponding carbon dioxide emissions. A lumped and distributed parameter model of the entire system is constructed to simulate the performance of the kiln under actual operating conditions. The model is able to predict accurately the temperature distribution along the different modules of the kiln and the operation of the many natural gas burners employed to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…Then, it is possible to propose alternatives to obtain better quality products, as well as to reduce processing the time and energy consumption. Several studies of thermal analysis in kilns can be found in the literature [32][33][34][35][36][37][38][39][40][41][42][43][44].Yu [32] developed a transient mathematical model for tunnel kilns. Using the model, the author was able to predict several parameters of the process, such as the temperature distribution in parts, energy consumption, heat losses, rate at which energy is accumulated, etc.…”
mentioning
confidence: 99%
“…Then, it is possible to propose alternatives to obtain better quality products, as well as to reduce processing the time and energy consumption. Several studies of thermal analysis in kilns can be found in the literature [32][33][34][35][36][37][38][39][40][41][42][43][44].Yu [32] developed a transient mathematical model for tunnel kilns. Using the model, the author was able to predict several parameters of the process, such as the temperature distribution in parts, energy consumption, heat losses, rate at which energy is accumulated, etc.…”
mentioning
confidence: 99%
“…Technological advances not only reduce emissions, but also save costs (Song and Wang, 2018), particularly in the ceramic industry (Mezquita et al, 2014;Milani et al, 2017;Cuviella-Suárez et al, 2019). In the past two decades, Huida Group Co. Ltd. has upgraded its facilities such as kilns and stoves to improve the energy efficiency.…”
Section: (A) Rates Of Fuel Savedmentioning
confidence: 99%
“…The fluid domain focuses only on the catalyst as ideally could be installed in the exhaust chimney of the real kiln. The boundary conditions of the 3D simulation are derived from the lumped and distributed parameter model of the entire kiln as detailed in [25]. In addition to the Navier-Stokes equation and the energy equation, the equation for the chemical reactions taking place in the catalyst are accounted for.…”
Section: Fig 2 Methane Conversion Yieldmentioning
confidence: 99%